Speaking in Tongues: The Only Sign of Reception of the Holy Spirit? - Obeng, E. A. (Africa Theological Journal, 1986)
Paul did not consider speaking in tongues the only sign of an individual's reception of the Holy Spirit. Even according to Acts, speaking in tongues was not the exclusive sign of receiving the Spirit.–D.J.H. Abstract Number: NTA31-1987-1-360
Keywords: Biblical Theology – Various Themes.